2018
DOI: 10.1159/000486781
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Diagnosis of Hydro(metro)colpos: A Series of 20 Cases

Abstract: Background: Hydrocolpos and hydrometrocolpos are rare malformations caused by accumulation of secretion due to congenital obstruction of the vagina. Hydro(metro)colpos may be isolated or can be combined with other malformations as part of a syndromic disorder. We report on a series of 20 cases with hydro(metro)colpos diagnosed prenatally, delineate the differential diagnoses, and illustrate the spectrum of associated malformations. Subjects and Methods: This was a retrospective study involving 20 fetuses with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 23 publications
0
21
0
2
Order By: Relevance
“…Posteriormente, nueve estudios fueron excluidos por no tener acceso al texto completo; finalmente, se incluyeron 74 publicaciones que cumplieron con los criterios de inclusión (Tabla 1). En las 74 publicaciones incluidas se encontraron 6 estudios observacionales retrospectivos (4, 13-17), 10 series de casos (10)(11)(18)(19)(20)(21)(22)(23)(24)(25) y 58 reportes de caso (12,, que incluyeron un total de 663 pacientes. La mayoría de las publicaciones fueron en India con 11 estudios (17,29,39,(44)(45)(46)(47)52,60,62,63), seguido de USA con 9 estudios (30,32,53,56,69,70,72,75,78), China (10,11,13,15,24,25,33,67) e It alia (4,20,23,34,37,51,66,…”
Section: Resultsunclassified
See 1 more Smart Citation
“…Posteriormente, nueve estudios fueron excluidos por no tener acceso al texto completo; finalmente, se incluyeron 74 publicaciones que cumplieron con los criterios de inclusión (Tabla 1). En las 74 publicaciones incluidas se encontraron 6 estudios observacionales retrospectivos (4, 13-17), 10 series de casos (10)(11)(18)(19)(20)(21)(22)(23)(24)(25) y 58 reportes de caso (12,, que incluyeron un total de 663 pacientes. La mayoría de las publicaciones fueron en India con 11 estudios (17,29,39,(44)(45)(46)(47)52,60,62,63), seguido de USA con 9 estudios (30,32,53,56,69,70,72,75,78), China (10,11,13,15,24,25,33,67) e It alia (4,20,23,34,37,51,66,…”
Section: Resultsunclassified
“…La población incluida presenta una edad media al diagnóstico de 16,8 años (0 a 53 años). Un reporte de caso de diagnóstico ecográfico antenatal (54), 4 de diagnóstico neonatal (22,26,38,50), 12 entre 1 y 12 años (28,37,48,51 ,52,59,61,66,73,78,80,82), 26 entre 13 y 19 años (27,29,30,32,39,41,42,(44)(45)(46)(47)49,55,56,58,60,63,(68)(69)(70)(71)(72)74,76,77,79) y 15 reportes de mayores de 20 años (31,(33)(34)(35)(36)40,43,53,57,62,64,65,67,75,81).…”
Section: Resultsunclassified
“…A retrovesical cystic mass in a female fetus usually represent a Mullerian structure filled with fluid. Mallman et al reported 20 cases which illustrate the spectrum of differential diagnoses, associated malformations and possible course of action (30). Most of the cases were detected in the late ultrasound screening, and only one in the second semester screening (median gestational age at diagnosis 30 weeks).…”
Section: Resultsmentioning
confidence: 99%
“…HMC can sometimes be part of several syndromes. One case series [12] [18,19], and renal, skeletal, ear, and cardiac malformations of Mayer-Rokitansky-Küster-Hauser syndrome [20,21]. It is difficult to distinguish McKusick Kaufman syndrome and Bardet-Biedl syndrome in the neonatal period.…”
Section: Discussionmentioning
confidence: 99%